Multikinase Inhibitor-Induced Hand–Foot Skin Reaction: A Review of Clinical Presentation, Pathogenesis, and Management - Kumutnart Chanprapaph (2018)
© 2016, Springer International Publishing Switzerland. Multikinase inhibitors (MKIs) are targeted cancer therapies designed to inhibit multiple tyrosine kinase pathways responsible for tumor proliferation, growth, and survival. These agents are more able to target cancer cells and possess better safety profiles than conventional chemotherapies. However, MKIs can produce significant cutaneous adverse events, hand–foot skin reaction (HFSR) being the most clinically significant. Although not life threatening, HFSR can lead to MKI dose modification, interruption, or termination, potentially limiting the anti-tumor effect. This article summarizes the current knowledge concerning the epidemiology, clinical presentation, pathogenesis, histopathology, prognostic implication, and current evidence-based prophylactic and reactive treatment options for MKI-induced HFSR. Its high incidence and significant impact on the quality of life emphasizes the great need to understand the pathogenesis and improve management of this condition.